2023
DOI: 10.1111/gcbb.13028
|View full text |Cite
|
Sign up to set email alerts
|

Biochar co‐compost improves nitrogen retention and reduces carbon emissions in a winter wheat cropping system

Abstract: Organic amendments, such as compost and biochar, mitigate the environmental burdens associated with wasting organic resources and close nutrient loops by capturing, transforming, and resupplying nutrients to soils. While compost or biochar application to soil can enhance an agroecosystem's capacity to store carbon and produce food, there have been few field studies investigating the agroecological impacts of amending soil with biochar co-compost, produced through the composting of nitrogen-rich organic materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 101 publications
0
15
0
1
Order By: Relevance
“…Organic beefsteak tomato ( Solanum lycopersicum ) was chosen as the crop for the column study. The rationale for selecting this crop is because it followed the wheat–tomato crop rotation at the field site (Gao et al., 2023). In addition, tomato holds a major role in the California vegetable industry, with the majority of acreage harvested in the Central Valley (USDA‐NASS, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic beefsteak tomato ( Solanum lycopersicum ) was chosen as the crop for the column study. The rationale for selecting this crop is because it followed the wheat–tomato crop rotation at the field site (Gao et al., 2023). In addition, tomato holds a major role in the California vegetable industry, with the majority of acreage harvested in the Central Valley (USDA‐NASS, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…An extensive literature review conducted by Agegnehu et al (2017) highlights the greater potential of biochar co-compost to positively impact soil ecosystem services, as compared to biochar or compost alone. Similarly, a more recent meta-analysis conducted by Wang et al (2019) also reveals a substantial gain in yield (39.7%) for cereal crops grown with biochar co-compost, though much remains unknown about how agroecosystems respond to biochar co-compost application (Gao et al, 2023). Furthermore, balancing ecological stewardship and high levels of crop production remains a difficult task to resolve (Tully & Ryals, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the positive effects of straw returning was the capture and reuse of nutrients that would have otherwise been lost during the straw removal from the agroecosystem, reducing the requirement of chemical fertilizers (Gao et al, 2023). Furthermore, straw returning can retain soil nutrients for a longer term compared with the use of chemical fertilizers alone (Siedt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…bacteria and fungi, biochar, chemical nitrogen fertilizer, diversity and function, network and modular pattern, straw return modes practices impacted a diverse set of soil microbial properties (Nie et al, 2018;Wang et al, 2019). Previous reports have suggested that a combination of straw and chemical fertilizers is considered the most beneficial treatment for soil bacteria communities and functions (e.g., increases in the richness of bacteria and fungi or the rate of N 2 fixation in soil); however, the effect is not always positive, which depends on straw characteristics, soil properties, and experiment conditions (Chen, Li, et al, 2022;Gao et al, 2023;Yang, Muhammad, et al, 2022). Notably, the turnover rate, stress tolerance, and nutritional requirements of bacteria markedly differ from fungi.…”
Section: Introductionmentioning
confidence: 99%
“…As a cost-effective and environmentally friendly soil amendment, biochar plays a huge role in improving soil nutrients conditions (Lian et al, 2020), enhancing crop growth and yield (Hale et al, 2020), and altering the composition of soil microbial. More importantly, an increasing number of research results confirm that biochar plays an undeniable role in reducing carbon emissions in agricultural production (Gao et al, 2023;Sun et al, 2021). Since Rondon et al (2005) first reported the decrease in N 2 O emissions followed by modifying the biochar soil amendment in a greenhouse test, employing biochar as a greenhouse gas emission control strategy for agricultural soils has become more appealing.…”
Section: Introductionmentioning
confidence: 99%